The Development of “Khao Hawm Mae Paya Tong Dam Black Rice” (Oryza sativa L.) Bar Mixed with Fried Pisang Mas (Musa Sapientum) - Lertnimitmongkol, Witit; Mongkontanawat, Narumol (Recent Science and Technology, 2020)
Khao Hawm Mae Paya Tong Dam Black Rice is a healthy traditional rice variety in the district of Kao Kitchakut in Chanthaburi province. Therefore, the objective of the research was to study the percentage ratio of “Khao Hawm Mae Paya Tong Dam Black Rice” (Oryza sativa L.) Bar mixed with Fired Pisang Mas (Musa Sapientum) which were 56: 0, 28:28, 31:25, 34:22, 37:19 and 40:16, respectively. The result was founded that the most satisfaction ratio of Khao Hawm Mae Paya Tong Dam Black Rice and Fried Pisang Mas was 37:19 at the statistical significance of p<0.05. For the physical properties, brightness (L*), red color (a*), blue color (b*) and hardness value were, 24.17, 0.84, 5.08 and 28.43 N, respectively. For the chemical properties, water activity (aw), moisture content, fat, protein, fiber, ash and carbohydrate were 0.25, 7.57 %, 11.48 %, 2.14 %, 19.42 %, 1.17 % and 58.22 % w/w, respectively. In addition, total plate count was less than 1 × 103 and yeasts and molds count was 10 CFU/g. Due to the consumer acceptance testing of 400 consumers, it was found that the consumers were moderately satisfied with the product showing the average score of 7.11.